The International Development of Network Organizations: The Case of ONLYLYON - Valdemarin, Stefano (Management international / International Management / Gestiòn Internacional, 2021)
This paper aims to explore the international development of network organizations. Our analysis is based on an in-depth case study on ONLYLYON, an organization promoting the city of Lyon worldwide through a network of more than 27,000 members. Based on 36 interviews with ONLYLYON members and 103 participant observations realized over two years and a half, our research explores the way ONLYLYON develops its network in Italy. The results show that the Uppsala model partially applies to network organizations and underline the role of interaction between the micro- and meso-levels in the process of network development.